Autologous platelet-rich fibrin promotes wound healing in cats - Changrani-Rastogi, Anamika; Swadi, Krutika; Barve, Mitali; Bajekal, Niyati (Frontiers in Veterinary Science, 2023)
Street cats commonly present large skin wounds that pose significant challenges in veterinary practice. Platelet-rich fibrin (PRF) is a second-generation platelet concentrate increasingly used in humans to promote wound healing. Ease of use and clinical success in humans has prompted interest in using PRF in veterinary practice. However, until now, there is no reported study on using autologous PRF in feline wound management. This study evaluated the effect of application of autologous PRF in cats with naturally occurring cutaneous wounds. 16 cats with full-thickness cutaneous acute/subacute wounds were randomly allocated to PRF or Control (standard care) groups. Each cat was enrolled for two weeks. PRF was prepared according to previously described procedures. PRF was applied on Days 1 and 4 in addition to standard wound care. Wound size was measured using tracing planimetry. Wound surface area was calculated using SketchAndCalcTM software on scanned tracing images. Average wound sizes at enrolment were 8.39 cm2 (Control) (standard deviation (SD) 5.08 cm2) and 9.18 cm2 (PRF) (SD 3.71 cm2) (range 2.42-15.97 cm2). By Day 14, the mean wound size for the Control group was 2.17 cm2 (SD 1.52 cm2) and for the PRF was 0.62 cm2 (SD 0.44 cm2) (P = 0.015). At Day 14, the PRF group showed mean 93.85% wound contraction with SD 3.66, while the control group showed mean 76.23% wound contraction with SD 5.30 (P = <0.0001). Based on the results, PRF could be further investigated to promote wound healing in cats as a low-risk and convenient adjunctive therapy.